Au nanoclusters/porous silica particles nanocomposites as fluorescence enhanced sensors for sensing and mapping of copper(II) in cells. (5th September 2019) - Wang, Shengxu; Yang, Boyu; Zhang, Zhuqing; Xu, Xiaowei; Li, Hui; Cheng, Guiru; Yang, Zekai; Du, Hao; Yang, Yizhou; Yang, Xudong
Abstract: In this work, we first report Au nanoclusters/porous silica particles nanocomposites as fluorescence enhanced sensors for selective and sensitive detection of Cu (II). As red-emitting GSH-protected Au nanoclusters (Au NCs) were self-assemble into porous silica particles (PSPs) after ultrasonic treatment. As a result, the Au NCs can be immobilized in the nano-channels of PSPs, which leads to the observation of an immobilized induced emission enhancement phenomenon. The photoluminscence (PL) intensity of the nanocomposites can enhance dozens of times compared with Au NCs. As a result, we obtain a novel PL enhanced sensor of Au NCs/PSPs nanocomposites with excellent PL properties. The as-prepared Au NCs/PSPs nanocomposites show good water-solubility, high stability, low toxicity, and exhibit a high PL quenching for reliable, sensitive and selective detection of Cu 2+ . The limit of detection can reach as low as 1 ppb. What is more, the Au NCs/PSPs nanocomposites also show sensitive detection of Cu 2+ in living cells. These properties provide the Au NCs/PSPs nanocomposites with promising PL sensors for Cu 2+ detection in various environmental and biological systems.